Shielding disk position in intra-operative electron radiotherapy (IOERT): A Monte Carlo study. (July 2018) - Alhamada, Husein; Simon, Stephane; Philippson, Catherine; Vandekerkhove, Christophe; Jourani, Younes; Pauly, Nicolas; Dubus, Alain; Reynaert, Nick
Highlights: A valid Monte Carlo model of IOERT accelerator head was created. The dosimetry of 4 clinical scenarios of shielding disk positions were verified. New fixation tool of the shielding disk was tested. New design of the disk that provides good coverage of the target was suggested. Abstract: Purpose: In IOERT breast treatments, a shielding disk is frequently used to protect the underlying healthy structures. The disk is usually composed of two materials, a low-Z material intended to be oriented towards the beam and a high-Z material. As tissues are repositioned around the shield before treatment, the disk is no longer visible and its correct alignment with respect to the beam is guaranteed. This paper studies the dosimetric characteristics of four possible clinical positioning scenarios of the shielding disk. A new alignment method for the shielding disk in the beam is introduced. Finally, it suggests a new design for the shielding disk. Methods: As the first step, the IOERT machine "Mobetron 1000" was modeled by using Monte Carlo simulation, tuning the MC model until an excellent match with the measured PDDs and profiles was achieved. Four possible shielding disk positioning scenarios were considered, determining the dosimetric impact. Furthermore, in our center, to prevent beam misalignment, we have developed a shielding disk equipped with guiding rods. Having ascertained a correct alignment between the disk and the beam, we can propose a new internal design of the shielding disk that can improve the dose distribution with a better coverage of the treated area. Results: All MC simulations were performed with a 12 MeV beam, the maximum energy of Mobetron 1000 and a 5.5 cm diameter flat tip applicator, this applicator being the most clinically used. The simulations were compared with measurements performed in a water phantom and showed good results within 2.2% of root mean square difference (RMSD). The misplacement positions of the shielding disk have dosimetric impacts in the treatment volume and a small translation could have a significant influence on healthy tissues. The D-scenario is the worst which could happens when the shielding disk is flipped upside down, giving up to 144% dose instead of 90% at the surface of the Pb/Al shielding disk. A new shielding design used, together with our alignment tool, is able to give a more homogeneous dose in the target area. Conclusions: The accuracy of shielding disk position can still be problematic in IOERT dosimetry. Any method that can ascertain the good alignment between the shielding disk and the beam is beneficial for the dose distribution and is a prerequisite for an optimized shield internal design that could improve the coverage of the treated area and the protection of healthy tissues.